1988
DOI: 10.1128/jb.170.8.3752-3755.1988
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing cell shape in the mutans group of streptococci

Abstract: Electron and light microscopic and growth studies of representatives of the diverse species of mutans streptococci revealed the cells to be either bacillary or coccoid in shape. Some strains changed from bacillary to coccoid if the HCO3-/K' ratio of the media was increased and from coccoid to bacillary if the ratio was decreased. Doubling times of rods and cocci were the same despite an HCO3/K+ ratio change between 0.008 and 2.84. For strain 10449S, no tested anions or cations substituted for HC03-or K+ to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…2Present address: Department ofMicrobiology and Immunology, College of Medicine, University of Oklahoma Health Sciences Center, Oklahoma City, OK 73190 5To whom correspondence and reprint requests should be addressed Coykendall et al (1971) also recognized this shape variation, and our work (Tao et al, 1987(Tao et al, , 1988 revealed that the bicarbonate-to-potassium ratio in growth media regulates the expression of shape of Streptococcus mutans strains NCTC 10449S and GS5, independent of growth rate, pH, and other culture medium constituents. When the ratio of bicarbonate-to-potassium is low, as in modified Jordan (JM) medium (Tanzer et al, 1973), the cells are bacillary; when it is high, as in FMC defined medium (Terleckyj et al, 1975) or in JM adjusted to the same high bicarbonate to potassium ratio as in FMC, the cells grow as cocci.…”
mentioning
confidence: 82%
“…2Present address: Department ofMicrobiology and Immunology, College of Medicine, University of Oklahoma Health Sciences Center, Oklahoma City, OK 73190 5To whom correspondence and reprint requests should be addressed Coykendall et al (1971) also recognized this shape variation, and our work (Tao et al, 1987(Tao et al, , 1988 revealed that the bicarbonate-to-potassium ratio in growth media regulates the expression of shape of Streptococcus mutans strains NCTC 10449S and GS5, independent of growth rate, pH, and other culture medium constituents. When the ratio of bicarbonate-to-potassium is low, as in modified Jordan (JM) medium (Tanzer et al, 1973), the cells are bacillary; when it is high, as in FMC defined medium (Terleckyj et al, 1975) or in JM adjusted to the same high bicarbonate to potassium ratio as in FMC, the cells grow as cocci.…”
mentioning
confidence: 82%
“…Interestingly, Streptococcus mutans NCTC 10449S was shown to adopt a rod-like or an ellipsoid conformation depending on the salt composition of the medium. 24,25 Similarly, planktonic cells of L. lactis IL1403 underwent ovococcus to rod transition in a particular medium. Biofilms grown in this medium had elongated cells at their surface, while bacteria not directly exposed to the medium were only ovococci.…”
Section: The Two Morphogenetic Machineries Modelmentioning
confidence: 99%
“…A high bicarbonate-to-K+ ra tio reportedly produces spherical cells, whereas a low bicarbonate-to-K* ratio results in bacillary cells. In terestingly, several incomplete septae corresponding to cell division sites were found in the bacillary forms of Streptococcus mutans 10449S [Tao et al, 1987[Tao et al, , 1988. In mitochondria, accumulation of P; is known to cause swelling [Klingenberg et al, 1974; D'arctangelo et al, 1987], It is tempting to speculate that a similar mechanism accounts for the presently ob served 'ballooning' or swelling of the bacteria grown in the presence of zinc ions.…”
Section: Ultrastructurementioning
confidence: 99%
“…Lack of ATP and the intracellular accumulation of P,, in turn, upset their chemiosmotic regulation. Recent publications indicate that morphological alterations in mutans streptococci may occur in response to the bicarbonate to potassium ratio in the growth medium [Tao et al, 1987[Tao et al, , 1988. A high bicarbonate-to-K+ ra tio reportedly produces spherical cells, whereas a low bicarbonate-to-K* ratio results in bacillary cells.…”
Section: Ultrastructurementioning
confidence: 99%
See 1 more Smart Citation